Pengaruh Harga Dan Kualitas Produk Terhadap Kepuasan Konsumen Rumah Makan Titian Akar di Natar Pada Masa Pandemi - Saputra, Ramadhan; Subing, Achmad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Era of globalization current, especially in sector, tourism is growing, of which is in the food industry. This survey was conducted to find out the influence of price and product quality on Satisfaction of Consumer at Restaurant. Titian Akar partially and simultan eously the population in this research is 2,407 with a research sample of 100 respondents based on consumer data from Titian Akar Restaurant by filling out a questionnaire. Normality is technique is in the form of validity test, reliability test, multiple linear regression, coefficient of determination, classical assumptions (normality test, multicollinearity test, heteroscedasticity test) and hypothesis testing. The results of the analysis ofmultiple linearregression: Y= 23.896 + 0.104X1 + 0.166X2 + The results of the T test are Price Variable (X1) the t-count value is 2.974 > from the t-table value of 1.984. Product Quality Variable (X2) with a t-value of worth 3.927 > from the t-table value of 1.984.) So that a significant which is < from a determined value of 0.05 so that it can be declared significant. Simultaneous testobtained F count (12,881) > F table (3,089). The results of the coefficient of determination R square) are obtained worth 0.418 or (41.8%,) Price and product qualityproduct has a positive effect on consumer satisfaction.